2021
DOI: 10.1111/sapm.12415
|View full text |Cite
|
Sign up to set email alerts
|

New finite volume approach for multidimensional Smoluchowski equation on nonuniform grids

Abstract: This present work is based on developing a deterministic discrete formulation for the approximation of a multidimensional Smoluchowski (Coalescence) equation on a nonuniform grid. The mathematical formulation of the proposed method is simpler, easy to implement, and focuses on conserving the first‐order moment. The new scheme resolved the issue of mass conservation along individual components in contrast to the existing scheme which focuses only on conservation of the total mass of all components. The validati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 49 publications
(134 reference statements)
0
5
0
Order By: Relevance
“…Several techniques are available in the literature to solve the PBEs numerically. Some popular methods are sectional methods, method of moments, semianalytical homotopy methods, and the Monte Carlo method. , A detailed review of these solution methods is available in ref . The Monte Carlo method is a probabilistic method that generates random numbers to obtain statistical approximations of the entities under consideration.…”
Section: Description Of the Process And State-of-the-artmentioning
confidence: 99%
“…Several techniques are available in the literature to solve the PBEs numerically. Some popular methods are sectional methods, method of moments, semianalytical homotopy methods, and the Monte Carlo method. , A detailed review of these solution methods is available in ref . The Monte Carlo method is a probabilistic method that generates random numbers to obtain statistical approximations of the entities under consideration.…”
Section: Description Of the Process And State-of-the-artmentioning
confidence: 99%
“…It was demonstrated that the CAT is highly accurate numerical approach to solve problems related to multidimensional PBEs, however, computationally expensive due to its notion of distributing particles properties to the neighbouring nodes. In contrast to the sectional methods, the FVSs [117,118,127,141] are highly accurate and efficient as no distribution of particles properties to the neighbouring nodes is required, that is, weights are added to the formulations for conserving the integral properties. It was shown that the FVSs are easy to extend for approximating problems in higher dimensions due to their simpler mathematical formulation and are robust to apply on any kind of uniform and non-uniform grids.…”
Section: Simultaneous Aggregation-breakage-2dmentioning
confidence: 99%
“…The second analytical solution used in this study is based on a size-dependent additive kernel 𝐴𝐴 𝐴𝐴𝑖𝑖𝑖𝑖 = 𝑉𝑉𝑥𝑥𝑥𝑖𝑖 + 𝑉𝑉𝑦𝑦𝑥𝑖𝑖 + 𝑉𝑉𝑥𝑥𝑥𝑖𝑖 + 𝑉𝑉𝑦𝑦𝑥𝑖𝑖 (Fernandez-Diaz & Gomez-Garcia, 2007;Singh, 2021): (A4)…”
Section: Case II the Size-dependent Kernelmentioning
confidence: 99%
“…where 𝐴𝐴 𝐴𝐴2 = 1 − exp(𝑀𝑀𝑀𝑀) is the dimensionless time and M is the total mass of the particles in the system. In this case, we take N 0 = 1 and 𝐴𝐴 𝐴𝐴𝑥𝑥0 = 𝐴𝐴𝑦𝑦0 = 10 −3 , which are 10 times greater than the values in Singh (2021) to rescale the time close to the first case. It is shown that there is good agreement between the predicted median volumes, the FSDs of V x and that the FSDs along the diagonal with the corresponding theoretical results (Figure A3) at t = 0, 1, 10, 50, and 60 s. Note that at t = 25 s, the modeled FSD along the diagonal is overestimated in larger size classes compared to the analytical FSD, whereas the results at other moments are in good agreement.…”
Section: Case II the Size-dependent Kernelmentioning
confidence: 99%